The Relationship between the Severity of Atopic Dermatitis and Sleep Quality in Widya Mandala Surabaya Catholic University Teaching Hospital Patients - Caecilia Elva; Oenarta, Dave Gerald; Djaputra, Edith Maria (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Atopic dermatitis is a chronic inflammatory skin disease that commonly begins during childhood. Most atopic dermatitis patients may experience symptoms that continue into adulthood. Itching is the characteristic symptom of atopic dermatitis. Over time, patients’ itching can lead to sleep disturbances. In fact, every human being requires sleep to maintain the balance of metabolism, calories, temperature, and immunity. If a person often lacks sleep, the risk of obesity, type 2 diabetes mellitus, hypertension, heart disease, stroke, deterioration of mental health, and premature death will increase. Purpose: To analyze the relationship between the severity of atopic dermatitis and sleep quality in Widya Mandala Surabaya Catholic University (WMSCU) teaching hospital patients. Methods: This is an analytic study with a cross-sectional research design. This study used the purposive sampling technique as its sampling method. A dermatologist used the Eczema Area and Severity Index (EASI) instrument, to assess the severity of atopic dermatitis in the samples, and Pittsburgh Sleep Quality Index (PSQI) questionnaire to assess their sleep quality. Result: The Mann-Whitney test showed a p value of 0.348 (p> 0.05). Conclusion: There is no significant relationship between the severity of atopic dermatitis and sleep quality in WMSCU teaching hospital patients.